Effect of palm-based tocotrienols and tocopherol mixture supplementation on platelet aggregation in subjects with metabolic syndrome: a randomised controlled trial - Gan, Yee Lin; Fu, Ju Yen; Lai, Oi Ming; Chew, Boon How; Yuen, Kah Hay; Teng, Kim Tiu; Nesaretnam, Kalanithi; Selvaduray, Kanga Rani; Meganathan, Puvaneswari (Nature Publishing Group, 2017)
Tocotrienols, the unsaturated form of vitamin E, were reported to modulate platelet aggregation and thrombotic mechanisms in pre-clinical studies. Using a Food and Drug Administration (FDA)-approved cartridge-based measurement system, a randomised, double-blind, crossover and placebo-controlled trial involving 32 metabolic syndrome adults was conducted to investigate the effect of palm-based tocotrienols and tocopherol (PTT) mixture supplementation on platelet aggregation reactivity. The participants were supplemented with 200 mg (69% tocotrienols and 31% α-tocopherol) twice daily of PTT mixture or placebo capsules for 14 days in a random order. After 14 days, each intervention was accompanied by a postprandial study, in which participants consumed 200 mg PTT mixture or placebo capsule after a meal. Blood samples were collected on day 0, day 14 and during postprandial for the measurement of platelet aggregation reactivity. Subjects went through a 15-day washout period before commencement of subsequent intervention. Fasting platelet aggregation reactivity stimulated with adenosine diphosphate (ADP) did not show substantial changes after supplementation with PTT mixture compared to placebo (p = 0.393). Concomitantly, changes in postprandial platelet aggregation reactivity remained similar between PTT mixture and placebo interventions (p = 0.408). The results of this study highlight the lack of inhibitory effect on platelet aggregation after short-term supplementation of PTT mixture in participants with metabolic syndrome.